The humanities : cultural roots and continuities. - Witt, Mary Ann Frese.; ... [et al.] (Houghton Mifflin, 1997)
This book is about: Earliest civilizations; The Greco-Roman and Judeo-Christian roots; Medieval cultures; The West African cultural root; ...